The safety of metamizole (Analgin): A critical look - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Analgin is among most popular analgetics that is widely sold in drugstores in Ukraine, but not all doctors and patients are familiar with all its effects.